New York DADA 1915-23 - Naumann, Francis M. (New York : Harry N. Abrams Inc. Publishers, 1994)
Duchamp, Marcel ; Picabia, Francis ; Man Ray ; Gleizes, Albert ; Roche, Juliette ; Crotti, Jean & Yvonne ; Varèse, Edgard ; Roché, Henri-Pierre ; Wood, Beatrice ; Tice, Clara ; Sheeler, Charles ; Schamberg, Morton ; Demuth, Charles ; Covert, John ; Stella, Joseph ; The Stettheimer Sisters ; Dreier, Katherine ; etc.
Engels
boek
Keywords: New York